Acid-Base Disorders: Interpretation of the Stewart Approach - Stanie, Shianita; Juni Kurniawaty; Sudadi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2026)
Comprehension of physiological consequences arising from acid-base disturbances, together with manageable factors such as ventilation and perfusion that rapidly affect acid-base balance, is essential for anesthesiologists. The application of the Stewart acid-base model has advanced the mechanistic understanding of acid-base physiology. This model incorporates shifts in ions, including Cl-, K+, Na+, and PO43-, as well as the buffering capacity of albumin, to detect acid-base disorders. The Stewart approach is superior for identifying subtle and otherwise undetectable metabolic changes. It is founded on three core principles: electroneutrality, dissociation equilibria of incompletely dissociated substances, and mass conservation. In the Stewart method, [HCO3-] and pH in body fluids represent dependent variables determined by three independent variables: total CO2, strong ion difference (SID), and total weak non-volatile acid concentration (ATOT), which is primarily governed by albumin and phosphate levels.